Whole-Brain Atrophy Rate in Idiopathic Parkinson’s Disease, Multiple System Atrophy, and Progressive Supranuclear Palsy - C. Guevara; K. Bulatova; G. J. Barker; G. Gonzalez; N. Crossley; M. J. Kempton (Parkinson's Disease)
In multiple system atrophy (MSA) and progressive supranuclear palsy (PSP), the absence of surrogate endpoints makes clinical trials long and expensive. We aim to determine annualized whole-brain atrophy rates (a-WBAR) in idiopathic Parkinson’s disease (IPD), MSA, and PSP. Ten healthy controls, 20 IPD, 12 PSP, and 8 MSA patients were studied using a volumetric MRI technique (SIENA). In controls, the a-WBAR was 0.37%±0.28 (CI 95% 0.17–0.57), while in IPD a-WBAR was 0.54%±0.38 (CI 95% 0.32–0.68). The IPD patients did not differ from the controls. In PSP, the a-WBAR was 1.26%±0.51 (CI 95%: 0.95–1.58). In MSA, a-WBAR was 1.65%±1.12 (CI 95%: 0.71–2.59). MSA did not differ from PSP. The a-WBAR in PSP and MSA were significantly higher than in the IPD group (p=0.004 and p<0.001, resp.). In PSP, the use of a-WBAR required one-half of the patients needed for clinical scales to detect a 50% reduction in their progression. In MSA, one-quarter of the patients would be needed to detect the same effect. a-WBAR is a reasonable candidate to consider as a surrogate endpoint in short clinical trials using smaller sample sizes. The confidence intervals for a-WBAR may add a potential retrospective application for a-WBAR to improve the diagnostic accuracy of MSA and PSP versus IPD.